A rare case of esophageal mucoepidermoid carcinoma successfully treated via endoscopic submucosal dissection - So Eun Jeun; Kyung Bin Kim; Bong Eun Lee; Gwang Ha Kim; Moon Won Lee; Dong Chan Joo (Korean Society of Gastrointestinal Endoscopy, 2024)
Esophageal mucoepidermoid carcinoma (EMEC) is a special subtype of esophageal malignancy, accounting for less than 1% of all cases of primary esophageal carcinoma. Pathologically, it consists of a mixture of adenocarcinoma and squamous cell carcinoma with mucin-secreting cells. Special staining for mucicarmine helps to diagnose EMEC. We present a rare case of EMEC successfully treated via endoscopic submucosal dissection (ESD). A 63-year-old man was referred to our tertiary hospital. On esophagogastroduodenoscopy, a 6-mm-sized subtle reddish depressed lesion was identified in the mid-esophagus. Diagnostic ESD was performed with a high suspicion of carcinoma. Histopathologic findings were consistent with EMEC which was confined to the lamina propria without lymphatic invasion. We plan to do a careful follow-up without administering adjuvant chemotherapy or radiotherapy. Due to the small volume of the lesion, establishing a diagnosis was difficult through forceps biopsy alone. However, by using ESD, we could confirm and successfully treat a rare case of early-stage EMEC.